Measurement Of Structure-Borne Noise From Road Input In A Motor Vehicle Cabin - Azma, Putra; Wong, Hee Kiong; Nawal Aswan, Abdul Jalil (AUN/SEED-Net JICA, 2014)
Vehicle interior noise has been an important aspect to determine quality of a vehicle since it affects the level of acoustic comfort of the passengers. This paper proposes a simple noise measurement technique to quantify the contribution of the structure-borne noise due to tire-road interactions. A subcompact sedan was used as the test vehicle in this study. The Sound Pressure Level (SPL) inside the cabin was measured in two conditions – i) laboratory test when the test vehicle was running on a dynamometer and ii) field measurement. In the laboratory measurement, the SPL was measured at the engine speed of 1000, 2000, 3000 and 4000 revolutions per minutes (RPM). In the field measurement, the SPL was measured when the test vehicle was running at a steady RPM and the vehicle speed in the range of 60 to120 km/hr. The results showed that there was a profound contribution of structure-borne noise from the tire-road interaction and aerodynamic excitation at frequency below 400 Hz. It can be concluded that the structure noise-born in a vehicle is possibly contributed from road input interaction, vehicle suspension system and aerodynamic excitation on the vehicle.